An Empirical Evaluation of a Programming Model for Context-Dependent Real-time Streaming Applications - Do, Xuan Khanh; Louise, Stéphane; Cohen, Albert; Dubrulle, Paul; Goubier, Thierry; Cudennec, Loïc; Doré, Philippe (CCSD, 2015)
International audience no abstract